2009
DOI: 10.1177/1094670509334187
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Emotional Reactions for Negative Services: The Impact of Efficacy Beliefs and Stage in Process

Abstract: This article examines consumers' emotional reactions for a specific negative service—a mammography screening test—and measures how such reactions are influenced by the consumer's stage in the screening process and her beliefs in the efficacy of the test. Stage in process moderates the relationship between test efficacy beliefs and stress, such that those obtaining screening tests feel more stress as their belief in the efficacy of mammography increases while those obtaining follow-up diagnostic tests feel less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Another issue to consider in the servicescape design is whether the service is a so‐called positive or negative service, the latter referring to a service where the customer must cope with unwanted or stressful situations (Gelfand Miller et al, 2009)—and if the demarcations between the two dimensions are always clear, or rather blurred, implying services to be ambivalent (positive and negative) at times. The demands for the servicescape are usually rather different depending on the positive, negative or ambivalent character of the service; for instance, in a nursing home, safety is typically valued over recreation and the potential positive character of the service may gain less emphasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue to consider in the servicescape design is whether the service is a so‐called positive or negative service, the latter referring to a service where the customer must cope with unwanted or stressful situations (Gelfand Miller et al, 2009)—and if the demarcations between the two dimensions are always clear, or rather blurred, implying services to be ambivalent (positive and negative) at times. The demands for the servicescape are usually rather different depending on the positive, negative or ambivalent character of the service; for instance, in a nursing home, safety is typically valued over recreation and the potential positive character of the service may gain less emphasis.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue to consider in the servicescape design is whether the service is a so-called positive or negative service, the latter referring to a service where the customer must cope with unwanted or stressful situations (Gelfand Miller et al, 2009)-and if the demarcations between the two dimensions are always clear, or rather blurred, implying services to be ambivalent (positive and negative) at The findings contribute to transformative service research by explaining how the feeling of home is connected to the transformative outcomes of nursing home customers. It also shows how servicescape design can enhance the well-being of vulnerable customers, which service researchers have scarcely studied so far (Rosenbaum, Seger-Guttman, et al, 2017).…”
Section: Extended Impacts Of the Servicescape (Beyond Residents) And ...mentioning
confidence: 99%
“…Although healthcare services are hostile, many people are forced to use them at some point in their lives ( Hellén & Sääksjärvi, 2011 ). Negative emotional states such as worry, uncertainty, and unease are frequently created in hospital settings ( Morgan & Rao, 2006 ; Berry & Bendapudi, 2007 ; Miller, Luce, Kahn, & Conant, 2009 ). Researchers have examined the association between emotions and service quality evaluations ( Mattila & Enz, 2002 ; Slåtten, 2011 ; Naami, & Hezarkhani, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of psychology, the importance of emotions has acquired a lot of attention, but it is lacking in the marketing literature (Hellén, 2010). Positive services are well researched when compared to negative services (Morgan & Rao, 2006;Berry & Bendapudi, 2007;Miller et al, 2009). Thus, the goal of this study is to determine the relationship between patients' happiness and satisfaction through patients' mood and perceived service quality at a healthcare setup.…”
Section: Introductionmentioning
confidence: 99%
“…Service failure provides a natural context in which to explore emotional resilience as research into customer disappointment (e.g., Estelami, 2000; Jang et al, 2013), anger (e.g., Strizhakova et al, 2012; Su et al, 2018), fear (Su et al, 2018), rage (e.g., Patterson et al, 2009; Surachartkumtonkun et al, 2013), revenge (e.g., Joireman et al, 2013; Obeidat et al, 2017), violence (C. Harris & Daunt, 2013), frustration (Van Steenburg et al, 2013) cynicism (Tran et al, 2022), and other reactions to negative service (Miller et al, 2009), suggest that better understanding individuals’ propensity for and ability to manage their emotions in consumption contexts has potential benefits for firms and other marketplace actors. Extant research has demonstrated that consumer satisfaction following service failures—which we argue is impacted by emotional resilience—affects their behavioral intentions (Cronin et al, 2000; Ma & Wang, 2021; Tran et al, 2022) and consequential downstream variables like consumer loyalty and referrals (Das et al, 2020), and, critically, the propensity to engage in negative word‐of‐mouth (Obeidat et al, 2017; Tran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%